Redefining the Taxonomic Boundaries of Genus Xanthomonas - Kanika Bansal; Sanjeet Kumar; Anu Singh; Arushi Chaudhary; Prabhu B. Patil (Taxonomy, 2023)
The genus Xanthomonas primarily comprises phytopathogenic species. By carrying out deep phylo-taxonogenomics, we recently reported that the genera Xylella, Stenotrophomonas, and Pseudoxanthomonas are misclassified and belong to the genus Xanthomonas. Considering the importance of Xanthomonas/Xylella as plant pathogens and to further determine the taxonomic and phylogenetic breadth of this genus, we extended our earlier study by including all the reported genera and families in the order. This investigation revealed that at least four more genera belong to the genus Xanthomonas, with a notable case being Lysobacter, after which the family and order are named. Similarly, our investigation also allowed us to reveal the expanded taxonomic breadth of the related genus Rhodanobacter. This finding of a major related genus that lacks plant pathogenic species will allow for taxonomy-based comparative studies. The phylo-taxonogenomic revelations were further supported by complete 16S rRNA-based sequence boundaries proposed for genus delineation. Accordingly, we propose a taxonomic revision of these major and closely related genera along with their constituent families within the order Lysobacteraceae (Xanthomonadaceae). The identification of a major related genus lacking plant pathogenic species will be important in investigating the origin and success of pathogenic species/lineages in the genus Xanthomonas.